Ethnic Disparities in EPA and DHA Intake in US Adults: Results from the NHANES 2011–2014 (P04-107-19). (13th June 2019) - Julián-Serrano, Sachelly; Dodd, Kevin; Angleró, Ivonne; Emenaker, Nancy
Abstract: Objectives: Recent studies suggest a large percentage of US adults are not meeting recommended dietary intakes for omega-3 polyunsaturated fatty acids (n-3 PUFA), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Meanwhile, the Institute of Medicine has yet to establish Dietary Reference Intakes for either EPA or DHA and some US populations may be particularly vulnerable. Therefore, we investigated dietary consumption and main food sources of EPA and DHA across racial and ethnic group potentially at-risk. We hypothesized differences in mean dietary intakes of EPA and DHA ( P < 0.05) may exist across targeted groups due to differences in ethnocentric dietary patterns. Methods: For these investigations, data from the NHANES 2011–2014 was analyzed. Group mean daily EPA and DHA intake in grams (g), along with 95% confidence intervals (CI), were computed from up to two 24-hour recall measurements in Hispanics, non-Hispanics whites and others (NHW), non-Hispanic blacks (NHB), and non-Hispanic Asians (NHA). For major food sources across race/ethnic group, the fractions of total intake (and corresponding 95% CIs) from each food item were calculated from the first day's 24-hour recall. Results: A total of 9848 individuals were included in this analysis, representing 21% Hispanics, 44% NHW, 23% NHB, and 12% NHA. As expected, significant differences ( P < 0.0001 for all tests) in mean intake were observed across racial and ethnic groups for energy, total/saturated/monounsaturated/PUFA fat, cholesterol, EPA, and DHA. NHB reported highest total PUFA intake (Mean: 19.60 g; 95% CI: 18.99–20.22) and NHA reported the lowest (Mean: 16.57 g; 95% CI: 15.86–17.27). However, NHA reported an intake 3x higher of EPA (Mean: 0.07 g; 95% CI: 0.06–0.07) and 2x higher of DHA (Mean: 0.12 g; 95% CI: 0.11–0.14) than other ethnic groups. For NHA, oily fish, which are food sources higher in EPA and DHA, were the largest total EPA and DHA contributors. On the other hand, main contributors to EPA and DHA in Hispanics were food sources lower in EPA and DHA. Conclusions: In summary, we observed EPA and DHA mean daily intakes differ significantly across racial/ethnic groups. Further studies assessing dietary n-3 PUFA intakes in the US population should include differences in ethnocentric dietary patterns. Funding Sources: This project was funded by the NCI Introduction to Cancer Research Careers.